Aurora a Overexpression and pVHL Reduced Expression Are Correlated with a Bad Kidney Cancer Prognosis. Issue 6 (21st May 2013) - Ferchichi, Imen; Kourda, Nadia; Sassi, Samia; Romdhane, Khaled Ben; Balatgi, Sarra; Cremet, Jean Yves; Prigent, Claude; Elgaaied, Amel Benammar
Abstract : We investigate the expression and localization of the tumor suppressor protein pVHL as well as the oncoprotein Aurora A kinase in kidney cancer. Both Aurora A kinase and pVHL protein status were evaluated using immunohistochemistry. The Aurora A expression is correlated with the Fuhrman grade and the TNM stage, while the pVHL expression is correlated with the capsule rupture and the TNM stage. Aurora A kinase expression increases in malignant tissue comparing to the non-malignant one. And there is a decrease in pVHL expression from the adjacent healthy tissues to the tumor`s ones. The two kinds of opposite tumor profiles display significant distribution difference according to TNM stages. It could be proposed that the absence of Aurora A protein associated with a strong expression of pVHL in clear cells kidney carcinoma are of good prognosis for the disease.